Factores determinantes del estado nutricional del folato y el rol de la variante genética C677T de la enzima metilen tetrahidrofolato reductasa (MTHFR) (2016)
ABSTRACT: Folate is an essential nutrient because mammals lack biological activity to synthesize. It different factors generate folate deficiency. Recent studies have identified that the C677T variant of the enzyme methylene tetrahydrofolate reductase (MTHFR), can play a role in serum folate concentrations (SFC) and red cell folate (RCF). The aim of this rewiev was to actualice some generalities of folate metabolism, factors related to its deficiency, biochemical indicators used to assess the nutritional status of folate and role of the C677T polymorphism of the MTHFR enzyme on the cycle of folate and methionine. It is necessary to design studies with representative samples corroborating the effect of polymorphisms on biochemical indicators of nutritional status of folate and determine the dose-response effect and contribute to modify the nutritional recommendations with the necessary scientific evidence.